GUB06‐046, a novel secretin/glucagon‐like peptide 1 co‐agonist, decreases food intake, improves glycemic control, and preserves beta cell mass in diabetic mice. (23rd October 2017) - van Witteloostuijn, Søren B.; Dalbøge, Louise S.; Hansen, Gitte; Midtgaard, Søren Roi; Jensen, Grethe Vestergaard; Jensen, Knud J.; Vrang, Niels; Jelsing, Jacob; Pedersen, Søren L.
Abstract : Bariatric surgery is currently the most effective treatment of obesity, which has spurred an interest in developing pharmaceutical mimetics. It is thought that the marked body weight‐lowering effects of bariatric surgery involve stimulated secretion of appetite‐regulating gut hormones, including glucagon‐like peptide 1. We here report that intestinal expression of secretin is markedly upregulated in a rat model of Roux‐en‐Y gastric bypass, suggesting an additional role of secretin in the beneficial metabolic effects of Roux‐en‐Y gastric bypass. We therefore developed novel secretin‐based peptide co‐agonists and identified a lead compound, GUB06‐046, that exhibited potent agonism of both the secretin receptor and glucagon‐like peptide 1 receptor. Semi‐acute administration of GUB06‐046 to lean mice significantly decreased cumulative food intake and improved glucose tolerance. Chronic administration of GUB06‐046 to diabetic db/db mice for 8 weeks improved glycemic control, as indicated by a 39% decrease in fasting blood glucose and 1.6% reduction of plasma HbA1c levels. Stereological analysis of db/db mice pancreata revealed a 78% increase in beta‐cell mass after GUB06‐046 treatment, with no impact on exocrine pancreas mass or pancreatic duct epithelial mass. The data demonstrate beneficial effects of GUB06‐046 on appetite regulation, glucose homeostasis, and beta‐cell mass in db/db mice, without proliferative effects on the exocrine pancreas and the pancreatic duct epithelium. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Herein, we report that intestinal expression of secretin is markedly upregulated in a rat RYGB model. Thus, a secretin‐GLP1 co‐agonist – GUB06‐046 – was developed. Chronic administration of GUB06‐046 to diabetic mice improved glycemic control and reduced HbA1c levels. Stereological analysis of pancreata revealed an increased beta‐cell mass, with no impact on exocrine pancreas mass or pancreatic duct epithelial mass, demonstrating beneficial effects on glucose homeostasis and beta‐cell mass, without proliferative effects on the exocrine pancreas and the pancreatic duct epithelium.